Land Markets and Labor Productivity: Empirical Evidence from China - Jian Zhang; Ashok K. Mishra; Peixin Zhu (Institute of Labor Economics (IZA), 2023)
This study investigates the impact of the land rental market (LRM) on labor productivity in rural China. Particular attention is given to farm and non-farm labor productivity. Using 2012 household-level data and a multinomial endogenous switching treatment regression (MESTR) technique, we find that rural households renting-in farmland increased labor productivity in the farm sector by about 55%, while labor productivity in the non-farm sector decreased by about 6%. We also find that rural households renting-out farmland had lower labor productivity in both the farm and non-farm sectors by 13% and 9%, respectively. More family labor transferred from the farm to the non-farm sector after renting-out land.
Keywords: C31; J22; Q15; Q18; 330; land rental market; labor productivity; farm sector; non-farm sector